Krótki opis długiej historii języka polskiego - Dunaj, Bogusław (Slavia Occidentalis, 2023)
The article offers an overview of the history of Polish language from the 9th century up to the present moment. The development of the Polish language was informed by two processes, namely, linguistic diversification, which caused dialectal differences, and integration, which contributed to the constitution of the literary language. The first half of the 16th century constitutes a critical period in the evolution of Polish language. It is then that the inception of the literary language took place. Here, the invention of print turned out to be a communicative breakthrough, predominantly because it facilitated language integration. Consecutive stages in the history of Polish language were connected with historic events, like the loss of Polish independence and its regaining. Such events brought about changes in the status of Polish language. The most recent period in the history of Polish language begins in 1989, when vital socio-political changes, as well as the information technology revolution took place. It is also the time when the integrative processes intensified, and began including geographical, as well as stylistic linguistic variations (predominantly, by the expansion of colloquial Polish into other functional varieties of the language).